Hazards of trichloroethylene on the liver in animals: A systematic review and meta-analysis - Hongwei Lou; Jianghong Yang; Qinghong Liu; Qin Yang (Emerging Contaminants)
A systematic review and meta-analysis were conducted, aiming to establish a scientifically grounded understanding of trichloroethylene (TCE)-induced hepatotoxicity. Relevant studies published prior to February 29, 2024 were meticulously searched. The standardized mean difference (SMD) was employed to assess the correlation between the control group and the TCE exposure group, while heterogeneity was quantified using the I2 index. After a thorough screening and exclusion process, a total of 57 articles met the eligibility criteria. Important parameters pertaining to liver health, such as ALT, AST, TNF-α, IL-1β, and others, were analyzed, resulting in the identification of 40 parameters related to liver injury. The results revealed that GLB, ALP, CYP2E1, GR, IL-6 (mRNA), and TGF-β (mRNA) did not exhibit statistically significant differences (P > 0.05). However, high heterogeneity was observed in indicators other than F4/80, EGR1 (mRNA), and MDA-protein adducts (P < 0.1, I2 > 50%). Notably, TCE exposure significantly increased the activity of ALT, AST, LDH, as well as the expression levels of TNF-α, IL-1β, TNFR1, IL-6, P65, P-P65, F4/80, IFN-γ, iNOS, C3a, TNF-α (mRNA), IL-1β (mRNA), IL-6R (mRNA), GP130 (mRNA), EGR1 (mRNA), CCL2 (mRNA), CCL5 (mRNA), iNOS (mRNA), liver coefficient, MDA, anti-dsDNA, MDA protein adduct, anti-MDA protein adduct antibody, and ANA. Conversely, TCE exposure decreased the activities of CAT, GPx, SOD, as well as the expression levels of Nrf2, TP, ALB, and GSH. Additionally, this study provided a comprehensive review of the two mechanisms underlying liver injury following TCE exposure. In conclusion, our findings furnish compelling evidence that TCE exposure induces liver injury, as manifested by alterations in various physiological indicators, including cytokines and oxidative stress-related markers, among others.